Drug utilization pattern evaluation and cost variation analysis of anti-fungal agents in tinea infected patients in dermatology department of a tertiary care teaching hospital - Modi, Ritu D.; Dumra, Gurusharan H. (International Journal of Basic & Clinical Pharmacology, 2023)
Background: Tinea infections are chronic superficial fungal infections, highly prevalent in tropical countries like India. Therefore, long-term therapy is needed and this can inflict a financial burden on the patients. Aim of the study was to assess drug utilization patterns in patients diagnosed with tinea infection and to evaluate the cost variability of anti-fungal agents. Methods: A cross-sectional observational study was conducted in patients for 3 months after taking permission from IEC. All adult patients already diagnosed with tinea infection were enrolled. Evaluation of drug utilization pattern was carried out using WHO core drug prescribing indicators and percentage of cost variability was calculated between different brands of anti-fungal agents. Results: A total of 252 patients were enrolled. Tinea corporis and cruris were the most commonly diagnosed tinea infection. Pruritus was the most common presenting symptom. Past history of similar illness was seen in 74 (29.4%) patients mean of 3.83±0.87 drugs were prescribed per patient. Drugs prescribed from NLEM was only 42.1%. Most commonly prescribed drugs were oral itraconazole and topical miconazole. Percentage of cost variability was seen maximum with capsule itraconazole 200 mg (237.5%) by oral route and luliconazole 30 gm (175.6%) by topical route. Conclusions: Prescribing practices of drugs can be improved by promoting generic drug and prescribing drugs from NLEM. Wide range of cost variation can lead to high economic burden in tinea infected patients.